Puzzling out presynaptic differentiation - Pinto, Maria J. (2017)
Proper brain function in the nervous system relies on the accurate establishment of synaptic contacts during development. Countless synapses populate the adult brain in an orderly fashion. In each synapse, a presynaptic terminal loaded with neurotransmitters-containing synaptic vesicles is perfectly aligned to an array of receptors in the postsynaptic membrane. Presynaptic differentiation, which encompasses the events underlying assembly of new presynaptic units, has seen notable advances in recent years. It is now consensual that as a growing axon encounters the receptive dendrites of its partner, presynaptic assembly will be triggered and specified by multiple postsynaptically-derived factors including soluble molecules and cell adhesion complexes. Presynaptic material that reaches these distant sites by axonal transport in the form of pre-assembled packets will be retained and clustered, ultimately giving rise to a presynaptic bouton. This review focuses on the cellular and molecular aspects of presynaptic differentiation in the central nervous system, with a particular emphasis on the identity of the instructive factors and the intracellular processes used by neuronal cells to assemble functional presynaptic terminals. We provide a detailed description of the mechanisms leading to the formation of new presynaptic terminals. In brief, soma-derived packets of pre-assembled material are trafficked to distant axonal sites. Synaptogenic factors from dendritic or glial provenance activate downstream intra-axonal mediators to trigger clustering of passing material and their correct organization into a new presynaptic bouton. This article is part of a mini review series: "Synaptic Function and Dysfunction in Brain Diseases".